USAGE OF SOCIAL MEDIA IN DISSEMINATING AGRICULTURAL INFORMATION AMONG EXTENSION FARMERS INSOUTH WESTNIGERIA - Popoola, O.P.; Okoro, N.O.; Alao, O.M.; Yakubu, S.; Uyamasi, I.M.; Adara, C.T. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined the usage of social media in disseminating agricultural information among extension farmers in South-West Nigeria. A multi-stage sampling technique was used to select 299 respondents across Ekiti, Oyo, and Osun States. Data were analyzed using descriptive statistics. Results revealed that farmers were predominantly male (65.9%) with an average age of 49 years, indicating an active and productive farming population. Most respondents had some level of formal education, which may support ICT adoption. Findings further showed that farmers possessed low knowledge of most social media tools, except WhatsApp (Mean = 2.19), generator as power support = 2.18), Zoom ( = 2.17), and Facebook ( = 2.11). Effectiveness ratings indicated that Facebook, email, WhatsApp, Zoom, video calls, and GPS were perceived as most effective among extension workers, while farmers rated blogs, Facebook, and video calls higher than other platforms. The study concludes that although social media holds great potential for agricultural information dissemination, farmers’ limited knowledge of key platforms restricts optimal use. Strengthening digital literacy is recommended.